Rearing larvae of dusky grouper, Epinephelus marginatus (Lowe, 1834), (Pisces: Serranidae) in a semi-extensive mesocosm | La cría de larvas de mero, Epinephelus marginatus (Lowe, 1834), (Pisces: Serranidae), en un mesocosmos de tecnología semiextensiva - Cunha, M. E. (2014)
One of the major obstacles to propagating dusky grouper, Epinephelus marginatus, is the difficulty of rearing the early larvae. We have successfully raised dusky grouper larvae in mesocosms using a mixed diet of endogenous plankton grown in the rearing tank and an exogenous supply of Brachionus plicatilis and Artemia sp. Newly hatched larvae at an initial density of 1.3 ind.l-1 were stocked in partially shaded 3 m3 circular outdoor tanks during the summers of 2007 and 2008. Before introducing newly hatched larvae, the water was left for six days to promote plankton growth. Larval growth occurred at two different rates: i) a faster rate from first feeding to the beginning of metamorphosis, and ii) a slower rate at transformation. Survival at the beginning of metamorphosis was less than 10% (33 DPH) in 2007 and between 25 and 50% (25 DPH) in 2008. High mortalities were observed during larval transformation. The estimated minimum food requirement per grouper larvae increased more than 300% from the beginning of the notochord flexion to the beginning of metamorphosis. To meet such a high feeding requirement the number of larger prey organisms/copepods in the mesocosm should be eight times higher during this time period.